Colour-optimized quantum yields of Yb, Tm Co-doped upconversion nanocrystals. (6th February 2019) - Kraft, Marco; Würth, Christian; Palo, Emilia; Soukka, Tero; Resch-Genger, Ute
Abstract: We present here a systematic analysis of the influence of Tm 3+ doping concentrations ( x Tm ) on the excitation power ( P )-dependent upconversion luminescence and -performance of hexagonal-phase NaYF4 : 20% Yb 3+, x Tm % Tm 3+ upconversion nanoparticles (UCNPs) for x Tm of 0.2, 0.5, 0.8, 1.2, and 2.0, respectively. Our results reveal the influence of these different Tm 3+ doping concentrations with respect to optimized upconversion quantum yield (Φ UC ) values of the various Tm 3+ upconversion emission bands, with the highest Φ UC values of the Tm 3+ emission bands above 700 nm resulting for different x Tm values as the Tm 3+ emission bands below 700 nm. This underlines the potential of Tm 3+ dopant concentration for colour tuning. Special emphasis was dedicated to the spectroscopic parameters that can be linked to the (de)population pathways of the various Tm 3+ energy levels, like the P - and x Tm -dependent slope factors and the intensity ratios of selected emission bands. The evaluation of all parameters indicates that not only energy transfer upconversion-, but also cross-relaxation processes between neighbouring Tm 3+ ions play a vital role in the (de)population of the excited energy levels of Yb 3+, Tm 3+ codoped nanocrystals.